2023
DOI: 10.1038/s41419-023-05675-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of G protein subunit alpha i2 as a promising therapeutic target of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a global health problem. Its incidence and mortality are increasing. Exploring novel therapeutic targets against HCC is important and urgent. We here explored the expression and potential function of Gαi2 (G protein subunit alpha i2) in HCC. The Cancer Genome Atlas Liver Hepatocellular Carcinoma (TCGA-LIHC) database shows that the number of Gαi2 transcripts in HCC tissues is significantly higher than that in the normal liver tissues. Moreover, Gαi2 overexpression in HCC correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Recent investigations highlight the significant role of Gαi2 protein in the proliferation of cancer cells 26 , 27 . In a study by Chen et al, Gαi2 over-expression was identified as a pivotal factor in promoting the growth of hepatocellular carcinoma (HCC) cells 27 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigations highlight the significant role of Gαi2 protein in the proliferation of cancer cells 26 , 27 . In a study by Chen et al, Gαi2 over-expression was identified as a pivotal factor in promoting the growth of hepatocellular carcinoma (HCC) cells 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations highlight the significant role of Gαi2 protein in the proliferation of cancer cells 26 , 27 . In a study by Chen et al, Gαi2 over-expression was identified as a pivotal factor in promoting the growth of hepatocellular carcinoma (HCC) cells 27 . Silencing or knockout (KO) of Gαi2 led to mitochondrial dysfunction, apoptosis, and growth arrest in HCC cells, impeding HCC xenograft growth in nude mice 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation